If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4+4(8-3x)=-2(2+3x)+8
We move all terms to the left:
-4+4(8-3x)-(-2(2+3x)+8)=0
We add all the numbers together, and all the variables
4(-3x+8)-(-2(3x+2)+8)-4=0
We multiply parentheses
-12x-(-2(3x+2)+8)+32-4=0
We calculate terms in parentheses: -(-2(3x+2)+8), so:We add all the numbers together, and all the variables
-2(3x+2)+8
We multiply parentheses
-6x-4+8
We add all the numbers together, and all the variables
-6x+4
Back to the equation:
-(-6x+4)
-12x-(-6x+4)+28=0
We get rid of parentheses
-12x+6x-4+28=0
We add all the numbers together, and all the variables
-6x+24=0
We move all terms containing x to the left, all other terms to the right
-6x=-24
x=-24/-6
x=+4
| x+.05x=134.69 | | -72+7x+2x²=0 | | 3+6x=9x-21 | | m-31=31 | | 7x+4*(2x-3)=(60x+24)/(-2) | | 5(3+y)-2=8 | | x+.07x=125.03 | | (3a-2)/2=8 | | -0.25x=-1.25 | | –9=2x–5 | | -.0.25x=-1.25 | | h/6−1=3 | | 4x+16=x+16 | | 3x^2=100x+10000 | | 2(4x+5)+8=9+4(3x+1) | | 8/5+3x+7/10=-1 | | x+22=10 | | 8x+66=-2x-24 | | 2x-24=-5x+32 | | 7x+13=-3x+3 | | 1-(y-2)=5+y | | -3x-24=-9x-66 | | -3x+21=2x-24 | | 3x-17=-3x+19 | | 7x+31=-2x-14 | | 10x+74=7x+53 | | (3x-40)=(2x+20) | | 8m+4=4m+12 | | 25+10x-x^=7 | | 3y–12=52+y | | 8x+21=-10x-15 | | -7x-39=-4 |